A value at risk analysis of cedit default swaps - Burkhard Raunig; Martin Scheicher (European Central Bank (ECB), 2008)
We investigate the risk of holding credit default swaps(CDS) in the trading book and compare the Value at Risk (VaR) of a CDS position to the VaR for investing in the respective firm's equity using a sample of CDS – stock price pairs for 86 actively traded firms over the period from March 2003 to October 2006. We find that the VaR for a stock is usually far larger than the VaR for a position in the same firm's CDS. However, the ratio between CDS and equity VaR is markedly smaller for firms with high credit risk. The ratio also declines for longer holding periods. We also observe a positive correlation between CDS and equity VaR. Panel regressions suggest that our findings are consistent with qualitative predictions of the Merton (1974) model.
Keywords: E43; G12; G13; 330; credit default swap; Structural Credit Risk Models; Value at Risk; Börsenkurs; Kreditderivat; Kapitalbeteiligung; Risikomaß; Vergleich; Kapitalstruktur; Welt